Bridging the Gap of Voter Apathy: A Framework for Inclusive and Enhanced Electoral Participation in Zimbabwe - Arthur Fidelis Chikerema; Vincent Chakunda (2023)
At the turn of the new millennium, the African continent witnessed a series of ‘democratised’ elections marking a paradigm shift from the traditional trajectories of violent overhauls and state power usurpation. Observably; this was celebrated globally as the illumination of democracy in the African continent. However, out of elections, a culture of apathy has been born with a serious problem negatively affecting voter turnout across the continent. Reports have indicated that the elections discourse is marred by military subversion of the people’s will, overt violence and intimidation, hijacking of voters roll, blurred voters registration exercises and fraudulent voter procedural adjectival systems. The research traced, distinguished and examined the causative factors and trends of voter apathy in Africa with particular reference to Zimbabwe. The study also aimed to understand the unique socio-political, socio-ethnic and socio-economic circumstances that drive negative determinations, beliefs and attitudes assisting the persistence of voter apathy in Zimbabwe. The first elections held in Zimbabwe marked the nation’s monumental voter turnout of 94%, since then, voter turnout began to drop noticeably in subsequent years. Held (2010) agreed that deep seated social exclusion, political disenfranchisement and politician’s acts of corruption and fanning violence have had a bearing on voter turnout. In spite of loss of confidence in elections as panacea to any meaningful democratic transformation in Zimbabwe, the research impelled conventional wisdom for epic voter turnout and electoral participation by framing a plausible and imperative scheme for comprehensive and enhanced elections, which shall restore a high pulse rate of inclusive political participation of the Zimbabwean electorate. This is supported by Dalton (2007:2) who posits that, “Without public involvement in the electoral process, democracy lacks both its legitimacy and its guiding force.” Despite Dalton’s view, the meaning and quality of election has been a cause for concern as citizens have been disenfranchised by politicians and this has affected the enthusiasm of the electorate in Africa with particular reference to Zimbabwe’s political landscape and the voting process. The research was premised on a qualitative research design approach. The research targeted 3consticuencies per province (Midlands, Manicaland and Matebeleland North, Harare, Mashonaland east and Mashonaland) since elections have been held under different conditions and political atmosphere and this require context specific examination. Respondents were selected using a tripartite sampling approach as developed by the researchers and this involved three sampling techniques in their order as follows: stratified sampling, systematic random sampling and purposive sampling. Data was collected using a combination of questionnaires and in-depth interviews and were analysed using two main techniques: critical discourse analysis and trend analysis The research explored various mechanisms to enhance electoral participation in Africa with particular reference to Zimbabwe and boost the electorate confidence to be involved in the voting process.